A new methodology for virtual water level Gauges - Chemin, Yann H. (2016)
Monitoring water stored in lakes and reservoirs is much needed in various countries for energy generation, food security and mitigating floods, among recurrent global issues. Natural and human-made open water bodies do not all have monitoring systems, this lack of regular information generates uncertainties in modeling, and increases unaccounted time-bound residuals in water balances. A large amount of water bodies storage variations are not monitored around the World. Here we show that this can be changed by the creation and the implementation of the concept of water Level Virtual Gauges (wLVGs) based on slope tracks upstream of water bodies, correlated to publicly available satellite remote sensing information returning water levels bi-monthly on average, sometimes weekly. An operational RMSE is found to be 12-52 cm height, depending on the characteristics of the upstream slopes used to calibrate wLVGs. This methodology is simple enough to be implemented for all medium to large reservoirs, but is alsofound successful for smaller rural reservoirs in tropical/sub-tropical countries. We anticipate that this can open globally distributed pathways to monitor open water bodies across the World, improve public databases on water storages and give management information for non/less-monitored water bodies.